2014
DOI: 10.1111/cfs.12140
|View full text |Cite
|
Sign up to set email alerts
|

‘It's about the whole family’: family contact for children in kinship care

Abstract: A B S T R AC TContact with family for children in care is identified as a right under the United Nations Convention on the Rights of the Child. However, such contact often presents challenges because of the protective concerns that have led to care arrangements being made. The Family Links: Kinship Care and Family Contact research study explored the nature and extent of family contact in kinship care, with a particular focus on the circumstances that create positive contact and foster family relationships. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Our informants found this instability very demanding, and it made them worry a lot, including worries of the parent's death. This underpins former research on the complexity of the relationships between children and parents with SUD and the need for professional support to cope with it (Alexanderson & Näsman, 2017;Bath, 2015;Forrester, Holland, Williams, & Copello, 2016;Kiraly & Humphreys, 2016;McWey & Mullis, 2004;Wilson et al, 2012).…”
Section: Sud As a Choice Or A Diseasementioning
confidence: 82%
See 1 more Smart Citation
“…Our informants found this instability very demanding, and it made them worry a lot, including worries of the parent's death. This underpins former research on the complexity of the relationships between children and parents with SUD and the need for professional support to cope with it (Alexanderson & Näsman, 2017;Bath, 2015;Forrester, Holland, Williams, & Copello, 2016;Kiraly & Humphreys, 2016;McWey & Mullis, 2004;Wilson et al, 2012).…”
Section: Sud As a Choice Or A Diseasementioning
confidence: 82%
“…Research suggests that the content of the contact is more important than frequency and visits should take place in home-like environments, be emotionally safe and informal, and should include activities (Haight, Kagle, & Black, 2003;Kiraly & Humphreys, 2013;McWey et al, 2010). There is a need for professional support and supervision of children, parents, and foster parents in order to improve the quality of the contact (Kiraly & Humphreys, 2016).…”
mentioning
confidence: 99%
“…Conversely, contact can be disruptive and prevent children developing a sense of permanence, particularly if negative attitudes between foster carers and parents are communicated to children (Morrison et al 2011). Carers highlight the negative experiences of children and young people from unreliable, disinterested or outwardly rejecting parents (Neil et al 2003;Moyers et al 2006;Kiraly & Humphreys 2014). It has been suggested that poorly planned, poor quality and unsupervised contact may even be harmful, particularly where there is a history of maltreatment (Sinclair et al 2005;Sen & Broadhurst 2011).…”
Section: Introductionmentioning
confidence: 99%
“…; Moyers et al . ; Kiraly & Humphreys ). It has been suggested that poorly planned, poor quality and unsupervised contact may even be harmful, particularly where there is a history of maltreatment (Sinclair et al .…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this group of carers was initially piqued by our earlier survey of formal (statutory) kinship carers in Victoria, Australia (in the United Kingdom, known as “kinship foster carers”), that explored children's experiences of family contact (Kiraly & Humphreys, ). To our surprise, one fifth of the 430 respondents were not related to the children in their care.…”
Section: Introductionmentioning
confidence: 99%